PENGARUH REGULASI DIRI TERHADAP PERILAKU KONSUMTIF PADA MAHASISWA PENGGUNA DOMPET DIGITAL DI UNIVERSITAS HKBP NOMMENSEN MEDAN - Berto Abadi Putra Sinaga; Freddy Butarbutar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of self-regulation on consumptive behavior among university students who use digital wallets at Universitas HKBP Nommensen Medan. The development of digital wallets provides convenience, speed, and efficiency in conducting transactions, but it may also increase students’ tendency to make impulsive and excessive purchases. This study employed a quantitative approach with an associative research design. The research subjects consisted of 350 active students of Universitas HKBP Nommensen Medan who use digital wallets. The sample was selected using purposive sampling. Data were collected using self-regulation and consumptive behavior scales in the form of Likert scales and were analyzed using simple linear regression with the assistance of SPSS 20.0. The results showed that self-regulation had a significant effect on consumptive behavior, with an F-value of 75.131 and a significance level of 0.000 < 0.05. The R value of 0.421 and R Square value of 0.178 indicate that self-regulation contributed 17.8% to the variation in consumptive behavior, while the remaining 82.2% was influenced by other factors outside the study. The regression coefficient of -0.374 indicates that self-regulation had a negative effect on consumptive behavior. Thus, the higher the level of students’ self-regulation, the lower their tendency toward consumptive behavior when using digital wallets.